The concept of norm applied to Spanish learning and its linguistic varieties in the Brazilian context - Venâncio da Silva, Bruno Rafael Costa (2021)
This article aims to discuss the concept of norm applied to the Brazilian context related to Spanish learning, especially focusing on the insertion of the linguistic variation phenomena in the classroom. We deal with the linguistic norm from two lines of work defined by Deoclécio and Bagno (2021): the teaching of foreign languages ​​from a polycentric perspective and linguistic education to promote tolerance and combat linguistic prejudice. To carry out this work, our theoretical framework is made up of Brazilian and Spanish-speaking researchers who discuss the norm from these two axes such as Andión, (2008), Bagno (2003), Fanjul (2011), Faraco and Zilles (2017) and Moreno Fernández (2007, 2008). In this way, it was possible to understand and differentiate the standardization processes of Spanish and Portuguese with the purpose of making Spanish teachers in Brazil aware of the different linguistic norms present in both languages. We consider that this knowledge is useful for the insertion of linguistic variation contents from a polycentric perspective in Spanish learning as proposed by Andión (2005, 2007), Andión and Casado (2014), Venâncio da Silva and Andión (2019) and Venâncio da Silva (2020).